E-LKPD DAN LITERASI LINGKUNGAN PADA PENDIDIKAN ERA REVOLUSI INDUSTRI 4.0: Pendidikan Era Revolusi Industri 4.0, Literasi Lingkungan, E-LKPD, dan Hubungan antara E-LKPD, Literasi Lingkungan pada Pendidikan Revolusi 4.0 - Jesiyanti Suni Amtonis (JURNAL KOULUTUS, 2022)
The development of the revolution to enter the industrial revolution 4.0 is marked by combining technology that is identical with limitations where almost all life has been converted from manual to digital so that this revolution has collaboration on education. To face the industrial revolution 4.0 education, every student needs to have knowledge, critical thinking skills and literacy skills (digital, information, media) and master ICT (technology, information and communication) and create new creative and innovative opportunities. This study aims to describe the educational process of the industrial revolution 4.0, environmental literacy and the need for E-LKPD. The method used is literature review or library research. The results of the literature review show that industrial revolution 4.0 education is one of the learning media needs is environmental literacy E-LKPD.